Promoting Coaches on Instagram: A Content Analysis of Posts Featuring NCAA Division I Coaches of Women’s Sports - Santia, Martina; Upton, Jodi; Hirko, Scott (Journal of Intercollegiate Sport, 2024)
Despite Title IX regulations, gender discriminatory practices in college sports continue to affect athletes, coaches, and administrative personnel at various levels. One manifestation of gender discrimination could affect the differential promotion of coaches via social media channels. This study investigates how NCAA Division I coaches across nine intercollegiate women’s sports are promoted on Instagram. We collected and analyzed a total of 649 Instagram posts from 98 official accounts of athletic departments across all 10 NCAA Division I-FBS conferences. Our findings indicate equitable promotion of female and male coaches for the same sports on social media. This suggests that social media could be disrupting the gender stereotypes that are deeply ingrained within the coaching profession and hinder women’s progress in sports. Future research steps and Title IX implications are discussed.